Cerebellum & ataxias (London : BioMed Central, 2014)
"Cerebellum & Ataxias is an open access journal devoted to cerebellar research and cerebellar disorders, including scientific reports and clinical cases of the numerous forms of ataxias."
Mode of access: World Wide Web.
Description based on: 1:1 (16 June 2014); title from journal homepage (BioMed Central website, viewed June 18, 2014).
Latest issue consulted: 4:16 (21 September 2017) (viewed November 1, 2017).
Keywords: Cerebellum -- Periodicals; Cerebellum -- Diseases -- Periodicals; Cerebellar ataxia -- Periodicals; Ataxia -- Periodicals; Ataxia; Cerebellar ataxia; Cerebellum; Cerebellum -- Diseases; Cerebellar Diseases; Cerebellum; Cerebellar Ataxia; Neuroscience; Electronic journals